Национально-культурные единицы языка в свете полипарадигмального анализа - Терехова, С.И. (Культура народов Причерноморья, 2013)
Статья содержит результаты научного исследования русского, украинского и английского
языков, посвященного полипарадигмальному анализу реалий, т. е. лексических единиц, содержащих в
своей семантике национально-культурный компонент (в т. ч. и референциальных репрезентаций). В ней
охарактеризованы результаты полипарадигмального анализа национально-специфической лексики на
основе модели функционально-семантического поля реалий, а также представлены критерии
типологизации анализируемого материала, специфика, которую следует принимать во внимание при
переводе, охарактеризованы способы перевода реалий.
Ключевые слова: лексика, функционально-семантическое поле, культуроним, реалия,
полипарадигмальный анализ, алломорфизм, изоморфизм. Стаття містить результати наукового вивчення російської, української та англійської мов,
присвяченого поліпарадигмальному аналізу реалій, тобто лексичних одиниць, які несуть у своїй
семантиці національно-культурний компонент (у т. ч. і репрезентацій референції). У ній
охарактеризовано результати поліпарадигмального анализу національно-специфічної лексики на основі
моделі функціонально-семантичного поля реалій, а також подано критерії типологізації, специфічні
характеристики аналізованого матеріалу, які слід мати на увазі при перекладі, розглянуто способи
перекладу реалій.
Ключові слова: лексика, функціонально-семантичне поле, культуронім, реалія, поліпарадигмальний
аналіз, аломорфізм, ізоморфізм. The article is devoted to the contrastive study of the verbal means that are used to embody of the
system of specific national and cultural units of lexicon in Ukrainian, Russian and English at the functionalsemantic
level of analysis, with a focus on verbal paradigms and words, including reference representations.
The article contains the results of the contrastive studies of the above mentioned languages. It is devoted to
multy-paradigmal approach on so called, words-realities, or units of national specific lexicon in the above
mentioned languages. The results of multy-paradigmal analyses of words with national and cultural elements in
their semantics are characterised here. Multy-paradigmal approach introduced in this research allowed to
additionally employing inclusion notional and associative analysis, which highlighted the way native speakers of
the contrasted languages conceptualize representations of national specific lexicon in their typical and specific
features. The research was conducted based on the model of functional-semantical field of national specific
words. The main criteria of classification of the analised language units as well as specific feachers of the words
under analyses are described in the article. The author stresses the idea that units of national specific lexicon
should be carefully studied in frames of multy-paradigmal analyses, as it gives the full detailed characteristics of
their forms, semantical extents, stylistic peculiarities as well as different connotations and associations of the
investigated language units.
Кey words: lexicon, functional-semantic field, units of national specific lexicon, realia, multy-paradygmal
analyses, allomorphism, isomorphism.